Wpływ urbanizacji na zmiany hydrogramu odpływu w zlewni Żylicy (Beskidy Zachodnie) - Holeksa, Szymon; Raciok, Mateusz; Absalon, Damian (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2017)
Mathematical models which transfer downfall to surface runoff are applied for a catchment whose area is smaller than 50 km2 and where high-water stages are caused by rainfall. The aim of the paper was to investigate changing hydrographs as a result of increasing urbanization. Calculations were performed using models which transfer effective rainfall into surface runoff. The modelling was carried out for three different periods which were characterized by different use: historical, current and predicted. Effective rainfall was transferred into surface runoff using Snyder’s model. Retention was calculated by SCS-CN model.
Keywords: Snyder’s model; modelling; urbanization; anthropogenic impact